STUDY OF THE PREVALENCE OF HOSPITAL-ACQUIRED INFECTIONS IN THE TERTIARY HEALTH CARE INSTITUTION: Point prevalence study of healthcare-associated infections - Djordjevic, Zorana; Marković, Tijana; Stojković, Milica; Petrović, Ivana; Zornić, Sanja; Marković Denić, Ljiljana; Rakić, Violeta (Medicinski časopis, 2024)
Healthcare-associated (HAIs) represent a major challenge to healthcare systems because they lead to increased morbidity, prolonged hospitalization with uncertain outcomes, and increased treatment costs. The aim of the study: is to assess the situation regarding BI in a tertiary level health care institution. Methods: HAI point prevalence study was conducted at the University Clinical Center Kragujevac (Serbia) during November 2022 within the national study. According to the method of the European Center for Disease Prevention and Control, trained teams collected data on patients who were admitted before 8 am in all departments of the hospital. Variables at the ward and patient level were analyzed. Results: 567 patients were included in the study, and the prevalence of patients with at least one HAI was 8.3%, and the prevalence of HAI was 8.6%. The highest prevalence were in adult (34.6%) and pediatric/neonatology (21.2%) intensive care units. Pneumonia was the most frequently registered type of HAI (32.7%), followed by urinary tract infections (28.6%), while surgical site infections and blood infections were equally represented (16.3%). Among the 50 isolates, 24 (48.0%) were bacteria from the order Enterobacterales, followed by gram-negative non-fermenting bacilli with 24% (Acinetobacter spp. 14 and Pseudomonas aeruginosa 5 isolates), and 9 (18%) isolates belonged to Gram-positive cocci . The isolated pathogens showed a high degree of resistance to the tested antibiotics. Multivariate logistic regression identified the following independent risk factors for HAI: prolonged hospital stay, worse McCabe score, patient intubation and use of antimicrobial drugs. Conclusion: The prevalence study enabled a quick overview of the basic epidemiological characteristics of HAI in our hospital and provided help in defining priorities for taking appropriate prevention measures.